2012
DOI: 10.1302/0301-620x.94b4.27648
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and symptomatic osteoarthritis of the knee

Abstract: Given the growing prevalence of obesity around the world and its association with osteoarthritis of the knee, orthopaedic surgeons need to be familiar with the management of the obese patient with degenerative knee pain. The precise mechanism by which obesity leads to osteoarthritis remains unknown, but is likely to be due to a combination of mechanical, humoral and genetic factors. Weight loss has clear medical benefits for the obese patient and seems to be a logical way of relieving joint pain associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 82 publications
0
46
0
5
Order By: Relevance
“…However, even if there is evidence in the literature that overweight precedes the development of OA [8,23], we cannot state whether the deficit in muscle mass existed before the development of OA. High BMI may be a risk factor for perioperative and postoperative complications [31]. Finally, one of the most important findings of this study may be the low BMI adjusted lean mass found in patients with hip OA, as this may have clinical implications.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, even if there is evidence in the literature that overweight precedes the development of OA [8,23], we cannot state whether the deficit in muscle mass existed before the development of OA. High BMI may be a risk factor for perioperative and postoperative complications [31]. Finally, one of the most important findings of this study may be the low BMI adjusted lean mass found in patients with hip OA, as this may have clinical implications.…”
Section: Discussionmentioning
confidence: 73%
“…A high prevalence of OA also has been reported in obese patients and in weightbearing joints [4,6], partly referred to a high joint surface load [31]. However, primary OA also has been seen in nonweightbearing joints such as the thumb base and fingers [33,35].…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that there is no need for general preoperative screening of low BMD when planning for knee arthroplasty. High BMI is known as a risk factor for peri-and postoperative complications [28], and this group of patients should then be regarded as a risk cohort in this aspect. Furthermore, weight loss should be encouraged in this group of patients to reduce the mechanical load over the joint, and the proportionally low muscle mass indicates that these patients both pre-and postoperatively should be subjected to intense physical training as to improve the muscle protective ability.…”
Section: Resultsmentioning
confidence: 99%
“…Local factors such as chronic repeated loads, loads with high magnitude, ligament instability, neuromuscular impairment, and joint deformity may accelerate the degenerative process [5]. A high prevalence of OA has been reported in obese patients and in weightbearing joints [3,5], often referred to as high joint surface load [28]. Primary OA can also be found in nonweightbearing joints such as the base of the thumb and the fingers [30,32], and there are also differences in prevalence of primary OA in men and women [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…В первую очередь, он вы-зван хирургическими инфекциями и венозной тромбоэмболией (ВТэ). Для артропластики риск развития сосудистых осложнений увели-чивается в 1,5 раза на каждые 5 кг/м 2 увеличе-ния ИМТ [54].…”
Section: ожирение и радикальный подход в лечении остеоартритаunclassified